Catalytic role of amines in activation of PhICl2 from a computational point of view. Issue 72 (18th August 2021) - Farshadfar, Kaveh; Ariafard, Alireza
Abstract : We thoroughly investigated mechanistic features of dichlorination of diazoacetates using PhICl2 catalysed by pyridine. Abstract : We thoroughly investigated mechanistic features of dichlorination of diazoacetates using PhICl2 catalysed by pyridine. We found that the pyridine serves as a catalyst for decomposition of PhICl2 to PhI and Cl2, leading to the dichlorination step being driven by the in situ generated Cl2 . This type of activation was found to be applicable to other amine-catalysed chlorination reactions using PhICl2 .